(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2010)
The present paper presents descriptions of 11 trepostome bryozoan species from the material deposited at the Geological Centrum Göttingen, Germany, and Nationaal Natuurhistorisch Museum (Naturalis), Leiden, Netherlands. The studied material comes from the Lower to Middle Devonian (Emsian-Eifelian) deposits of different localities in Cantabrian Mountains, NW Spain. Three species are new: Leptotrypella maculata n. sp., Anomalotoechus tabulatus n. sp. and Eifelipora tenuis n. sp. The genus Mongoloclema is reported for the first time from the Devonian of Europe. The described fauna displays palaeobiogeographic relations to the Lower Devonian (Pragian) of Bohemia and to the Middle Devonian of Kazakhstan and Michigan (USA).